Impact of Encapsulation Position in Pickering Emulsions on Color Stability and Intensity Turmeric Oleoresin - Ahreum Han; Youjin Baek; Hyeon Gyu Lee (Foods)
The emulsification of natural pigment is a widely utilized strategy to enhance its stability in the food industry. However, high turbidity in emulsions often causes color fading, limiting their application. Here, we developed a comprehensive Pickering emulsion (PE) system to improve the color intensity and stability of turmeric oleoresin (Tur) under various food processing conditions. Specifically, the effects of two encapsulation positions within the PE were compared: the inner oil phase (Tur-IPE) and the outer solid particle layer (Tur-OPE). Lysozyme and carboxymethyl cellulose nanoparticles (NPs) were used as natural solid particle surfactants, with their successful formation confirmed through physical property analysis and FTIR spectroscopy. The optimal oil fraction (φ) for suitable physical properties of PE was determined to be 0.2. Interestingly, Tur-OPE significantly exceeded Tur-conventional emulsions (Tur-CE) and Tur-IPE in terms of color vividness, exhibiting higher redness and lower lightness (p < 0.05). During thermal processing at 70 and 90 °C, all emulsions demonstrated significantly enhanced heat resistance, retaining 1.3 to 1.6 times more Tur, respectively, compared to unencapsulated Tur (free Tur) (p < 0.05). Furthermore, Tur’s pH instability was significantly overcome by encapsulation in all emulsion systems (p < 0.05). During 4 weeks of storage period, Tur-OPE demonstrated the highest retention rates, with the half-life of Tur increasing in the following order: free Tur < Tur-CE < Tur-IPE < Tur-OPE. Thus, we highlighted the important role of encapsulation position in PEs in improving and maintaining the color stability and vividness of natural pigments under various food processing conditions.